Effect of combined stress (salinity + hypoxia) and auxin rooting hormone addition on morphology and growth traits in six Salix spp. Clones - Quiñones Martorello, Adriana; Fernandez, María Elena; Monterubbianesi, María Gloria; Colabelli, Mabel Noemí; Laclau, Pablo; Gyenge, Javier (Springer Nature, 2019)
Willows plantations development could be an alternative for hydro-halomorphic soils but it is limited by combined stress salinity + hypoxia (main stressor under waterlogging conditions). We studied the effects of saline stress, alone or interacting with hypoxia, on growth, morphology and rooting process of six willows clones, assessing also whether rooting hormone (H, Indol Butyric Acid) contributes enhancing rooting under combined stress. Three hybrids of Salix matsudana × Salix alba (Sm×Sa), two of Salix babylonica × Salix alba (Sb×Sa) and a Salix nigra (Sn4) clone were evaluated in hydroponics. Ten treatments were generated combining salinity [moderate (MS): 5 dS/m, and high (HS): 10 dS/m]; hypoxia (with or without artificial aeration, HypO), and presence or absence of H. After 120 days, shoot and root biomass, root number and length, and hypertrophied lenticel number were evaluated. Contrary to what was expected, Sm×Sa and Sb×Sa hybrids showed no adverse additive effects of combined stress compared with saline stress; whereas in Sn4, S + HypO favored root biomass production increasing number and elongation of roots. Salinity was the main limiting factor for root production, being only MS conditions compatible with rooting, although limited. There was no common response in relation to H addition. In Sn4, H potentiated the effects of MS + HypO on root biomass, increasing number of roots. However, it had no positive effect on biomass production in the remaining hybrids, producing a higher root number but shorter in length. More effort is needed to understand the physiological mechanisms behind the response to combined stress in willows.